2012
DOI: 10.5430/wje.v2n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Errors of Novice Java Programmers

Abstract: This descriptive study determined which of the sources of errors would predict the errors committed by novice Java programmers. Descriptive statistics revealed that the respondents perceived that they committed the identified eighteen errors infrequently. Thought error was perceived to be the main source of error during the laboratory programming exercises. Factor analysis showed that there were five categories for the types of errors committed. Four of them were symbol- or keyword-related errors (Invalid symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 39 publications
(56 reference statements)
0
16
0
2
Order By: Relevance
“…-Peter J Mellalieu [37] constructed a mining based feature rich prototype Decision Support System (ReXS) with spreadsheet mining to provide his students the provisions to predict their personal academic success and final grade as they progressed through a first-year course 'Innovation and Entrepreneurship'. -R. P. Bringula [38] could able to determine which of the sources of errors would presage the errors committed by tyro Java programmers. Factor analysis showed that there were five categories for the types of errors committed.…”
Section: Student Performance Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Peter J Mellalieu [37] constructed a mining based feature rich prototype Decision Support System (ReXS) with spreadsheet mining to provide his students the provisions to predict their personal academic success and final grade as they progressed through a first-year course 'Innovation and Entrepreneurship'. -R. P. Bringula [38] could able to determine which of the sources of errors would presage the errors committed by tyro Java programmers. Factor analysis showed that there were five categories for the types of errors committed.…”
Section: Student Performance Evaluation Methodsmentioning
confidence: 99%
“…R. P. Bringula [38] could able to determine which of the sources of errors would presage the errors committed by tyro Java programmers. Delineate statistics brought out that the respondents perceived that they committed the identified eighteen errors infrequently.…”
Section: Mjayakameswaraiah and Sramakrishna [28] Conducted A Study mentioning
confidence: 99%
“…To date, several studies have been conducted to identify student misconceptions of programming. Notably, novice misconceptions of programming are one of the biggest concerns to programming educators and students (Bringula, Manabat, Tolentino, & Torres, 2012; Kaczmarczyk, Petrick, East, & Herman, 2010; Özdener, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bringula et al [3] studied the sources of programming errors of novice Java programmers (i.e., students). The authors found out that thought error was the main reason why novice programmers committed programming errors.…”
Section: Difficulty In Learning Programmingmentioning
confidence: 99%
“…Programming is one of the core and desirable skills of computing students (e.g., Computer Science, Information Technology, and Information Systems) [3]. In fact, according to JobStreet.com [6], programmers topped the list of highest paid professionals for new graduates in the Philippines.…”
Section: Introductionmentioning
confidence: 99%